2015
DOI: 10.4049/jimmunol.1401352
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl tRNA Synthetase–Interacting Multifunctional Protein 1 Acts as a Novel B Cell–Activating Factor In Vitro and In Vivo

Abstract: Endogenous B cell–activating factors play pivotal roles in defense mechanisms by regulating B cell responses. We previously reported that aminoacyl tRNA synthetase–interacting multifunctional protein 1 (AIMP1) functions as a novel proinflammatory cytokine that activates macrophages and dendritic cells. However, roles of AIMP1 in B cell responses have not been studied. In this study, we investigated the effects of AIMP1 on B cell responses and their underlying mechanisms. AIMP1 induced the expression of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Extracellularly, AIMP1 activates innate immune cells such as macrophages and monocytes to produce inflammatory cytokines through MAPK signaling [43] and induces maturation of BMDCs [44]. AIMP1 potentiates the link between innate and adaptive immunity by activating NK cells [45] and B cells [46] and by promoting IL-12-mediated T-helper type 1 (T H 1) cell immunity [47]. AIMP1 expression in BMDCs directly promoted T H 1 cell polarization, which is characterized by the secretion of IL-12 and IFN-γ from antigenpresenting cells and T cells, respectively, and is associated with the generation of cell-mediated adaptive immune responses [48].…”
Section: The Role Of Aimp1 In Innate and Adaptive Antiviral Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellularly, AIMP1 activates innate immune cells such as macrophages and monocytes to produce inflammatory cytokines through MAPK signaling [43] and induces maturation of BMDCs [44]. AIMP1 potentiates the link between innate and adaptive immunity by activating NK cells [45] and B cells [46] and by promoting IL-12-mediated T-helper type 1 (T H 1) cell immunity [47]. AIMP1 expression in BMDCs directly promoted T H 1 cell polarization, which is characterized by the secretion of IL-12 and IFN-γ from antigenpresenting cells and T cells, respectively, and is associated with the generation of cell-mediated adaptive immune responses [48].…”
Section: The Role Of Aimp1 In Innate and Adaptive Antiviral Immunitymentioning
confidence: 99%
“…AIMP1 is also secreted as a full-length form or as a 22 kDa Cterminal EMAPII domain [99]. Secreted AIMP1 displayed diverse biological functions, including upregulation of proinflammatory genes [43] and activation of immune cells [46,100]. The EMAPII domain activated host immune responses by acting as a proinflammatory cytokine or as a chemoattractant to induce endothelial/mononuclear cell migration [99,101,102].…”
Section: Secreted Arss Acting As Cytokines and Chemokinesmentioning
confidence: 99%
“…Earlier studies demonstrated that genetic ablation of AIMp1 significantly enhanced T H 2‐polarized airway hyperreactivity in a model of allergic inflammation, 44 while in vitro studies showed that recombinant AIMp1 protein induced upregulated IL‐12 secretion from bone marrow‐derived DC and enhanced the generation of IFN‐γ‐secreting CD4 + T‐cells 43,45 . Recombinant AIMp1 also induced B‐cell activation, proliferation, and class switch recombination toward the T H 1‐specific IgG 2 isotype with increased antigen‐specific antibody production 46 . More recent work demonstrated that dendritic cell ‐expressed AIMp1 is a critical component of the T H 1 regulatory cascade and absolutely required for IL‐12 production, downstream T H 1 polarization, and functional antiviral and antitumor immunity in C57BL/6 and 129Sv mice 29 …”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that aaRS-interacting multifunctional protein 1 (AIMP1), an aaRS-associated factor, stimulated the activation of immune cells, including DCs, B cells, and NK cells (7,15,16). As AIMP1 and KRS are capable of activating macrophages and are closely associated within the multisynthetase complex (17,18), we, therefore, questioned whether KRS affects the phenotypes and functions of DCs.…”
mentioning
confidence: 99%